Price, Service Quality, and Purchasing Decision in Artist Management Services - Effendi Siregar, Emil Yusrin; Widjayanti, Arifiani (Journal of Business Administration Economics & Entrepreneurship, 2024)
The purpose of this study is to determine the influence of price and quality of service on the decision to purchase a product/service for artist management services at RRY Management. The independent variables in this research are price (X1), service quality (X2) and the dependent variable is purchasing decision (Y). Primary data for 2019-2023 is the type of data used in this study. The research method was quantitative approach. Multiple regression analysis was used for data analysis. According to the results of the simultaneous test (F), price and service quality significantly influence the purchasing decision. Meanwhile, the partial test (T) shows that price significantly influences the purchase decision and service quality significantly influences the purchase decision. Keywords: price, service quality, purchase decision